Antithrombotic Therapy Recommendations in the European Society of Cardiology Guidelines: How Robust Are the Randomized Controlled Trials Underpinning Them? - Santos, Catarina M. dos; Prada, Luísa; David, Cláudio; Costa, João; Ferreira, Joaquim J.; Pinto, Fausto J.; Caldeira, Daniel (TH Open, 2021)
Introduction Criticisms have been raised against the sole use of p-value in interpreting results from randomized controlled trials (RCTs). Additional tools have been suggested, like the fragility index (FI), a measure of a trial's robustness/fragility, and derivative measures. The FI is the minimum number of patients who would have to be converted from nonevents to events, in the group with the least events, for a result to lose statistical significance.Objective This study aimed to evaluate RCT supporting European Society of Cardiology (ESC) guidelines regarding antithrombotics, using the FI and FI-related measures.Methods FI, fragility quotient (FQ), and FI minus LTF lost to follow-up (FI − LTF) were calculated for the RCT underpinning recommendations regarding antithrombotic therapy from the updated ESC guidelines. LTF was compared with FI. Results were calculated for the total group of studies, as per guideline and as per recommendation type.Results Overall, 61 studies were included. The median FI was 24.5 (interquartile range [IQR]: 9.0–60.0) and median FQ was 0.0035 (IQR: 0.0019–0.0056). Median FI − LTF was 2.0 (IQR: 0.0–38.0). Twenty (32.8%) of the studies had one primary or main safety outcome with LTF exceeding FI. Peripheral arterial disease guideline and chronic coronary syndrome guideline had the lowest (2.5; IQR: 1.8–3.3) and the highest (48.5; IQR: 23.8–73.0) FI, respectively.Conclusion The median FI suggests robustness of clinical trials evaluating antithrombotic drugs cited in the guidelines, but about one-third of them had LTF larger than FI. This emphasizes the need for assessing trials' robustness when constructing guidelines.
Keywords: anticoagulant agents; antiplatelet agents; cardiovascular system; fibrinolytic therapy; health planning recommendations